On ‘being Australian’: Korean migrants in ‘post-multicultural’ Australia. - Ruth Phillips (Cosmopolitan Civil Societies: An Interdisciplinary Journal, 2021)
This paper reports on the findings of research into what Korean Australians thought about the process of ‘becoming and being Australian’, drawing on measures of social cohesion and ‘Australianness’. The aim of the research was to find out what Korean Australian migrants valued or were uncomfortable with in relation to multiculturalism and processes of ‘being Australian’, or conformation with ‘Australianness’. Based on in-depth interviews with ten and a survey of 153 members of the Korean migrant community in Sydney, data indicated that social activities and self-perception of identity effectively continue to reflect past Australian policy settings that recognised the importance of multiculturalism as both a community-based policy framework as well as a national social policy. The study found participants highly valued Korean identity, language and community and that bonds to the Korean community, limited English language competency and experiences of racism reinforced the importance of settling into a society that valued multiculturalism.